Sosialisasi Dan Penerapan Instalasi Prototipe Panel Surya 150 WP di SMK Prudent School Kota Tanggerang - Royhan, Muhamad; Dorand, Pietra; Nurhayati, Ade; Fachrur Rozi, Nurwan Reza (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2024)
As a power plant, the sun can produce unlimited light. Use of solar panels as a transformation device that transforms solar energy into electricity. The electricity produced is sent to the battery and stored as an emergency resource. Much appreciated for progressed innovation, sun-oriented boards can be utilized as a substitution for current power; in any case, the State Power Enterprise still gives power. SMK understudies can learn the significance of the plan and utilization of sun-based boards. In the other stage, SMK understudies will utilize model sun-based boards to introduce the coach given. Through the execution and socialization of sun-powered boards, SMK Judicious School City Tangerang works as arranged, and understudies can introduce models accurately from control to stack. Understudies and instructors will get fabric and explanations of current advancements within the most recent sun-oriented modules to empower advanced improvement.